ANALYSIS OF SOLAR FUEL FLOW FROM THE MAIN TANK TO THE MAIN ENGINE THROUGH THE PROCESS OF THE FUEL OIL PURIFIER ENGINE - Jafri, Muhamad; Musus, Yanres S. (SAINSTEK, 2019)
ABSTRACT Diesel fuel is a distillation product of crude oil that is specifically used as fuel for Compression Ignition engine, and in Indonesia diesel fuel is regulated with Directorate General of Oil and Gas, Regulation Number: 002/P/DM/ Oil and Gas / 2007. Diesel fuel must be free of impurities such as water and sand. The presence of fine sand that is mixed by diesel fuel can result of the wear of the fuel injector. Fuel purifier machine is a tool to be used to separate liquid and sludge so that damage to the engine due to the use of unclean fuels can be reduced. The purpose of this study was to analyse the flow of diesel fuel flow from the fuel purifier on the KN-Nipa ship, the Class II Navigation District-ship in Kupang. The research method was used was a direct measurement of the diesel fuel volume during a certain period. The results of the analysis show that the average flow rate of diesel fuel produced by the F.O Purifier machine is 202.86 litres/hour. These results are no different from the results of previous studies that was conducted by Paulus Pongkessu (2011), where during normal times, the flow of diesel fuel is 250 litres/hour, whereas when over flow occurs 1250 litres/hour. Keywords: F.O purifier machine; Sludge; Auxiliary engines